Comparison between night market and hypermarket retail formats' choice for fresh fruits and vegetables (FFV) purchase in Klang Valley, Malaysia using S-O-R model - Gindi, Abdullahi Auwal (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
There are several retail formats in existence in Malaysia competing for fresh fruits and vegetables consumers’ loyalty. On the other hand, fresh fruits and vegetables consumers are always evaluating which of these fresh fruits and vegetables (FFV) retail formats to choose for their FFV purchases. This study employs Stimulus – Organism – Response (S-O-R) model to compare consumers format choice between FFV night market and hypermarket retail formats and to evaluate the impact of demographic factor (income level) of consumers on their choice of retail formats for FFV purchases. A consumer’s survey was conducted with 700 respondents in Klang Valley Area, Malaysia. Based on the empirical results of night markets and hypermarkets’ retail formats, the model significantly fits for the two retail formats’ and income level is not a moderator on the relationships between stimulus and response for the two retail formats’ models.